2001
DOI: 10.1097/00000539-200106000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Propacetamol Reduces Morphine Consumption After Spinal Fusion Surgery

Abstract: We sought to determine the analgesic efficacy, opioid-sparing effects, and tolerability of propacetamol, an injectable prodrug of acetaminophen, in combination with morphine administered by patient-controlled analgesia (PCA) after spinal fusion surgery. Forty-two patients undergoing spinal stabilization surgery were randomized into two groups, which were given either an IV placebo or an IV injection of 2 g propacetamol every 6 h for 3 days after surgery. The postoperative opioid analgesic requirement was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 22 publications
4
82
0
11
Order By: Relevance
“…Our study is in agreement with the study of Joaquin Hernandez-Palazon et al (2001), 27 who demonstrated the usefulness of propacetamol as an adjunct to PCA morphine in the treatment of postoperative pain after spinal fusion.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is in agreement with the study of Joaquin Hernandez-Palazon et al (2001), 27 who demonstrated the usefulness of propacetamol as an adjunct to PCA morphine in the treatment of postoperative pain after spinal fusion.…”
Section: Discussionsupporting
confidence: 93%
“…Studies of combination treatment showed that paracetamol has an opioid-reducing effect and that it significantly reduces the patient's need for total opioids, thereby increasing the patient's overall satisfaction with the analgesic therapy (10,13). In the current study, we found Data are presented as means ± SD or as absolute numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature intravenous paracetamol is mostly used in settings of post-operative pain management (20,(24)(25)(26)(27). In a study by Moller et al, it was tried to compare the analgesic efficacy and safety of a single intravenouse infusion of 1 gram of acetaminophen with propacetamol 2 gram (a pro drug form of paracetamol) and placebo in patients with moderate-to-severe pain after third molar surgery.…”
Section: Discussionmentioning
confidence: 99%